The Effect of Soil Cover on Local Temperature Variations; Naranjo, Alajuela, Costa Rica, 2016 - Barrientos-Ávila, Enzo (2018)
The study aims to relate the variations in local temperatures in the central district of Naranjo, Alajuela, through the use of Landsat 8 images and Geographic Information Systems. A vectorization of the soil cover was carried out, and the areas of the different coverings were compared with the areas of the temperature ranges obtained, showing a relationship between high temperatures and urban areas and low temperatures and areas with vegetation. Showing the relationship between coverage and temperature is important to establish effective mitigation and adaptation measures in the face of climate changes and thus to avoid effects associated with urban areas such as the heat islands.